2004
DOI: 10.1038/sj.cgt.7700678
|View full text |Cite|
|
Sign up to set email alerts
|

In vivo rejection of tumor cells dependent on CD8 cells that kill independently of perforin and FasL

Abstract: Perforin/granzyme B-and Fas/FasL-mediated killing pathways are the main effector mechanisms of CTL and NK cells in antitumor immune responses. In this study, we investigated the relative role of these two lytic mechanisms in protection of the host from tumor progression, as well as spontaneous metastasis, using the D122 Lewis lung carcinoma and its gene-modified cells. Utilizing perforin knockout mice (B6-PKO) and Fas and FasL mutant (B6-MRL and B6-Smn) mice, we found that perforin expression in the host plays… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 44 publications
1
12
0
Order By: Relevance
“…Although a CCL19-induced TH1-polarized immune response could Cr-release cytotoxicity assay in splenocytes from CCL19-treated mice did not show any enhancement of cytotoxic activity compared with splenocytes from mice vaccinated with pDNA (b-gal) alone. Given the fact that a CCL19-induced increase of tumor rejection was observed in vivo, there are different possible explanations for this discrepancy: (1) chromium release assay does not necessarily detect all cytotoxic mechanisms displayed by effector cells 15 and in vivo rejection of tumor cells by CD8 þ T cells that kill independently of perforin and FasL have been described, 16 (2) CCL19-induced antitumor effects could be mediated (in part) by cells other than T cells. Finally, weak cytotoxic activity might be inherent to the b-gal mouse model and has previously been described.…”
Section: Discussionmentioning
confidence: 99%
“…Although a CCL19-induced TH1-polarized immune response could Cr-release cytotoxicity assay in splenocytes from CCL19-treated mice did not show any enhancement of cytotoxic activity compared with splenocytes from mice vaccinated with pDNA (b-gal) alone. Given the fact that a CCL19-induced increase of tumor rejection was observed in vivo, there are different possible explanations for this discrepancy: (1) chromium release assay does not necessarily detect all cytotoxic mechanisms displayed by effector cells 15 and in vivo rejection of tumor cells by CD8 þ T cells that kill independently of perforin and FasL have been described, 16 (2) CCL19-induced antitumor effects could be mediated (in part) by cells other than T cells. Finally, weak cytotoxic activity might be inherent to the b-gal mouse model and has previously been described.…”
Section: Discussionmentioning
confidence: 99%
“…Dobrzanski et al (11) reported that although tumor cytolysis was predominantly perforin-dependent in vitro, the therapeutic effects of CTL-based immunotherapy were dependent, in part, on effector cell -derived LTa in a B16 lung metastasis model. Furthermore, it has been shown that both D122 Lewis lung carcinoma and melanoma were rejected by tumor-specific CTLs through a cytolytic mechanism that was independent of both perforin and Fas pathways in vivo (12,13). These studies suggest that other cytotoxic effector pathways, in addition to perforin and Fas/FasL, play significant roles in the inhibition of tumor growth.…”
mentioning
confidence: 86%
“…Perforin-deficient mice were reported to be more susceptible to tumor development in some models [5][6][7][8], while other studies found that perforin-deficient CTL were fully capable of exerting anti-tumor activity in vivo [9][10][11][12][13]. Similarly, CD95L-dependent effector mechanisms have been shown to be important in some models [14][15][16] but not in others [9,13,17]. The release of soluble factors represents an additional mechanism by which CD8 T cells could exert anti-tumor activity.…”
Section: Introductionmentioning
confidence: 99%